Japan's Remilitarization, Passive Constitutional Amendment Discourse - Silalahi, Alma Evelinda (Jurnal Diplomasi Pertahanan, 2021)
This journal aims to observe the Japanese remilitarization plan of some elements of Japanese politics to amend the Pacifism constitution in article 9 related to military capabilities and the factors behind it. Japan's plan to amend Article 9 is a step that is considered important to make it easier for Japan to fulfil its national interests in the field of defence and security in the Pacific and East Asia regions. A qualitative approach is carried out to observe the facts that occur and is followed by using several concepts in analysing the phenomenon. The data collection technique that will be used is to find library research data. The perspective of Neorealism, the Concept of National Interest and Foreign Policy are used as the basis and direction to answer issues related to Japanese remilitarization and the discourse on the amendment of Article 9 of the Japanese Pacifism Constitution and the reasons behind the plan.